Fluorescence imaging of individual ions and molecules in pressurized noble gases for barium tagging in 136Xe - N. K. Byrnes; E. Dey; F. W. Foss; B. J. P. Jones; R. Madigan; A. D. McDonald; R. L. Miller; L. R. Norman; K. E. Navarro; D. R. Nygren; NEXT Collaboration (Nature Communications)
Abstract The imaging of individual Ba2+ ions in high pressure xenon gas is one possible way to attain background-free sensitivity to neutrinoless double beta decay and hence establish the Majorana nature of the neutrino. In this paper we demonstrate selective single Ba2+ ion imaging inside a high-pressure xenon gas environment. Ba2+ ions chelated with molecular chemosensors are resolved at the gas-solid interface using a diffraction-limited imaging system with scan area of 1 × 1 cm2 located inside 10 bar of xenon gas. This form of microscopy represents key ingredient in the development of barium tagging for neutrinoless double beta decay searches in 136Xe. This also provides a new tool for studying the photophysics of fluorescent molecules and chemosensors at the solid-gas interface to enable bottom-up design of catalysts and sensors.